Representations of power relations over the minds and bodies in the novel Mu‘adzdzibatī: A sociology of literature perspective - Haulaturruslaniyyah Haulaturruslaniyyah; Ekawati Ekawati (Priviet Social Sciences Journal, 2026)
This study analyzes the dynamics of social and political power in Mu‘adzdzibatī, a novel by Moroccan writer and philosopher Bensalem Himmich. Using descriptive qualitative methods and a sociocritical approach, this study examines how literary works reflect power in society. The theory employed is Foucault’s theory of power relations, which focuses on how power controls individuals or society in both non-repressive and repressive ways. The results of the study indicate that this novel depicts an institutional environment in which power operates through two main dimensions: the minds and bodies of prisoners. Power relations over the mind are exercised through the manipulation of prison regulations and the exploitation of religious discourse. Meanwhile, power relations over the body are exercised through the manipulation of the prison environment (panopticism) and physical domination or torture. This study concludes that Mu‘adzdzibatī is a literary work that reflects a very real portrayal of the power behind prison life.